Determinants Of Pulmonary Tuberculosis Incidence In Sintang District - Uray B. Asnol; Rika Yuanita Pratama; Abil Rudi; Yolanda Montessori; Rizki Amartani; Wagiran Wagiran (International Journal of Health and Pharmaceutical (IJHP), 2024)
Pulmonary tuberculosis is an infectious disease that is still endemic in society. The research sites were in the villages of Tanjung Ria, Tanjung Hulu and Sungai Raya, Sepauk District, Sintang District, with a total of 78 cases of tuberculosis, consisting of old cases and new cases.The purpose of this study was to determine the factors causing the incidence of pulmonary tuberculosis in the community. This type of research is quantitative with a case control approach method retrospective. The sample in the study for the case group used the total sampling technique and the accidental sampling control group. Analysis using chi square significance level of 0.05. The results showed that there was a relationship between house ventilation and the incidence of pulmonary tuberculosis (OR=4.521), there was a relationship between the humidity of the house and the incidence of pulmonary tuberculosis (OR=4.343), there was a relationship between the floor of the house and the incidence of pulmonary tuberculosis (OR=4.000), there was a relationship between lighting and the incidence of pulmonary tuberculosis (OR=4.169), there is a relationship between house occupancy density and the incidence of pulmonary tuberculosis (OR=4.640), there is a relationship between work and the incidence of pulmonary tuberculosis (TB) (OR=3.571), there is a relationship between income and the incidence of pulmonary tuberculosis (TB) ( OR=9,277). Recommended for Communities in Tanjung Ria, Tanjung Hulu and Sungai Raya Villages, Sepauk District, Sintang District need to maintain compliance with housing sanitation standards and increase their economic level so that they become examples for communities in other villages.